(untitled) (E Conference Zone, 2022)
The Stirling Engine Generator is a sealed high efficiency “heat engine” that is driven by the radiant energy supplied from the sun or any other source of external heat. Invented by Robert Stirling, hence its name, nearly two hundred years ago, the Stirling cycle engine is a type of solar engine, or sun motor, which operates using the principal of thermodynamics alternating between the hot and cold temperature cycles of a working gas.